THE EFFECT OF DOUCHING TREATMENTS USING MANJAKANI SEEDS (QUERCUS INFECTORIA GALL) BOILED INTO WATER TO TOTAL COLONY OF STREPTOCOCCUS SP AND ESCHERICHIA COLI AMONG IUD ACCEPTORS WHO EXPERIENCED VAGINAL DISCHARGE - Ika Wijayanti; M. Nurhalim Shahib; Herri Sastramihardja (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2020)
Intra Uterine Device (IUD) is a safe, effective, and reversible device made of plastic or metal which is inserted into the uterus through the cervical canal to prevent pregnancy. One of side effects of IUD is leucorrhoea or fluoralbus that is a whitish, intermittent and increased amount of discharge from vagina. Leucorrhoea is the most common complaint of women using IUD as it may cause uterus reactions to a strange object with excessive vaginal discharge characterized by increased amount of vaginal mucus, yellowish or gray, itchy, smelly, and causing inconvenience. A Moist condition and discharge in vagina among IUD acceptors is a good environment for pathogenic bacteria growth including Streptococcus sp and Escherichia coli. One of alternative treatments from herbal remedies is manjakani seeds (Quercus infectoria gall). Empirically, manjakani seeds have been used to clean genital organs for prevention and treatment of vaginal discharge. The active subtances of the seeds are tannin, saponin, alkaloid, steroid, flavonoid, and trapezoid that are believed as an antibacterial effect. This study aimed to determine the effect of douching treatments using manjakani seeds (Quercus infectoria gall) boiled into water to the total colony of Streptococcus sp and Escherichia coli among IUD acceptors who experienced vaginal discharge. The research methods of the study utilized quasi experiments with one group pretestpostest design. The sampling technique was consecutive sampling with IUD acceptors suffering vaginal discharge in puskesmasSukajadi and ledeng, Bandung as the samples. The results showed based on statistical test, there was a significant difference between the number of colonies of Escherichia coli, streptococcus sp and complaints of leucorrea pre-test and posttest test of douching of boiled manjakani seeds with p value 0.05.